Are psychology theses published in Peru? An analysis of three top-ranked universities in the Scimago ranking - Mamani-Benito, Oscar Javier (2021)
In order to determine the characteristics and frequency of publication of psychology theses from three Peruvian universities with better positioning in the Scimago ranking, a descriptive study of document analysis wasconducted on 180 undergraduate theses approved in the period 2010 -2019. The search for articles was carried out in Google Scholar and the Scopus database. The results indicate that the theses in greater proportion are of correlational type (53.3%), oriented to a line of clinical and health psychology (51.1%), considering a high school type population (26.1%) and with a sample size between 51 to 200 participants (47.2%). Only three studies were published in indexed journals. It is concluded that the frequency of publication of theses from Peruvian universities that lead the Scimago Ranking is very low. This reveals the need to strengthen formative research and promote strategies to increase scientific production from the Peruvian undergraduate level.